2016
DOI: 10.20517/2394-5079.2015.59
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin: an adjuvant therapeutic remedy for liver cancer

Abstract: The molecular signalling pathways for hepatocellular carcinoma and hepatoblastoma have been extensively studied. The treatment of these highly vascular tumors mainly revolves around chemotherapy and surgery. Yet there is a high associated morbidity and mortality due to advanced stages, adverse effects owing to chemotherapy and recurrence. The role of Curcumin as an adjuvant remedy is explored in this article. Curcumin stimulates apoptosis of cancer cells, acts as anti-proliferative agent, has anti-angiogenic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…C60 has been studied, along with other antioxidants in the prevention and treatment of cancers of various types [33,34]. Dr. Shilpa Sharma at the All-India Institute of Medical Sciences has studied the impact of antioxidants on hepatocellular cancers [35,36].…”
Section: Prevention and Treatment Of Cancermentioning
confidence: 99%
“…C60 has been studied, along with other antioxidants in the prevention and treatment of cancers of various types [33,34]. Dr. Shilpa Sharma at the All-India Institute of Medical Sciences has studied the impact of antioxidants on hepatocellular cancers [35,36].…”
Section: Prevention and Treatment Of Cancermentioning
confidence: 99%
“…In many of these studies, activation of epithelial-mesenchymal transition [EMT] program has been suggested as the mechanism linked to acquisition of invasive phenotype and the subsequent systemic dissemination of the epithelial cancer cells [13]. Due to the high recurrence rates and development of adverse effects after therapy, as well as the fact that liver cancer is typically discovered at an advanced stage since the lack of symptoms during early stages of the disease, the current management of HCC is not satisfactory [14,15]. Recently, a considerable attention has been paid to the use of natural polyphenols as a prophylactic and therapeutic remedy for liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that Cur can inhibit the proliferation, invasion, and metastasis of liver cancer cells[ 6 ]. Cur has been demonstrated to inhibit the proliferation of hepatoma cell line (HepG2 cells) in a dose- and time-dependent manner[ 7 ]. The current preclinical model studies in vivo and in vitro have shown that Cur, along with other curcuminoids, has immense potential as a curative agent for liver cancer, based on its potent antioxidant and anti-inflammatory properties and its ability to regulate a variety of signaling mechanisms[ 6 ].…”
Section: Introductionmentioning
confidence: 99%